(untitled) (University of Khartoum Engineering Journal, 2022)
The aim of this study is to simulate a Fluid Catalytic Cracking (FCC) Regenerator, of a local refinery, using the Fluent Ansys.13 program and subsequently to investigate the impact of the change in geometry on the unit’s performance. Three different geometrical models of FCC Regenerator were simulated. The Solid Works program was used to build up the computational domain and the commercial CFD code Ansys-Fluent 13 was used for meshing, models setup and solving. Three cases were examined: base case with a single air inlet, case one with five air inlets, and case two with five air inlets, however with the catalyst inlet axis raised by 100%. The results showed that the carbon solid mass content (used to represent the coke) decreases from 0.39 to 0.23 in the base case and to 0.12 in case one and to 0.19 in case two for the regenerated catalyst. Case one resulted in a decrease in carbon content by 100%, with a carbon monoxide emission of 10ppm (the base case at a value of 200ppm) which increased in case two to 100ppm. Furthermore the impact of air mass flow rate in case one (best case) was investigated starting with a mass flow rate of 29.5kg/s. The flow rate was further increased by 100% and 200% which resulted in a carbon mass content of 0.092 and 0.08 respectively.